Risk Management Mitigation in the New Normal Era - Wijaya, Oscarius Yudhi Ari (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The mitigation of business risk management in the Covid 19 pandemic is a powerful means of controlling the transmission and easing of socio-economic interactions. To avoid Covid 19 transmission, business organizations should adopt new cultural behaviors that align with proper health protocols to avoid Covid 19 transmission. This is because there are differences in the behaviors of business organizations. This research uses a qualitative approach with a literature study. It focuses on business and management mitigation risk factors in Covid 19 pandemic, as well as their impact on its transmission. The results show that the Covid 19 pandemic risk impacts private businesses as well as the state as a public organization entity equally responsible for solving the problem. Furthermore, no business is ready with adequate risk management planning for Covid 19 transmission. This has an impact on the risk of uncertainty for business sustainability. Moreover, there needs to be a proper theoretical, conceptual, and empirical risk management mitigation of Covid 19 transmission. Consequently, this enhances the control of transmission in office and business place clusters.